ANALISIS KEMATANGAN SOSIAL PENGGUNA FASEBOOK KELAS X SISWA SMA NEGERI 4 PUJUD - Timer Simamora Timer Simamora; Tri Umari Tri Umari; R. Arlilizon Raja Arlizon (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
AbstractThis study aims to describe the level of sosial manurity fasebook asers class x students of SMAN 4 Pujud, the background due to a phenomenon seen in schools, namely: Research issues How social manurity picture fasebook users class x students of SMAN 4 Pujud. The method used in this research is descriptive method. Loction of the study are in SMAN 4 Pujud. Subjects in this studys  were students of class x in SMAN 4 Pujud taken with saturated sample technique. Data and data collection tool was a questionnaire in the from of social manurity in students’ fasebook asers SMAN 4 Pujud made by the researchers themselves based on the lattice with alternative answers often, sometimeand never. Data analysis technique using benchmark categories based formula Supranto ( 2008: 2) and the percentage formula (Anas Sudijono, 2004: 170). Conclusion the results of this study based on the results of the calculation of benchmarks fasebook user questionnaire social maturityin 4 PujudState high school students in middle category in accordance with the results of the analysis. As a follow up of this study can researchers rekomendasikan that stakeholders especially parents and teachers to determinethe level of social maturityfor students of fasebook users, as well as the impeacts that may affect students’ learning achievement and relationships both at school and in thecommunity. Next to the researcher is expected to conduct farther research in view of the present study only refers to thoseaspects that still need further improvement Keywords: Social, Maturity.